(untitled) (Medical Forum Monthly, 2024)
Objectives: To assess the natural history of Renal Disease in patients with Pre-eclampsia or Eclampsia. Study design; It was an observational study. Place and Duration of study: This study was conducted simultaneously at two tertiary care hospitals: Fatima Memorial Hospital, Lahore and Bhatti International Teaching Hospital, Kasur from March 2009 to January 2011. Patients and Methods; women presented with pre-eclampsia or/ and eclampsia were consectively selected for the study fulfilling the inclusion criteria. A total number of 220 patients were enrolled in this study. All parameters required for the study were done carefully as blood pressure, proteinuria, renal function tests, urinary creatinine, weight, primary or multiparous, any previous history of pre-eclampsia. These parameters are checked at three and then six months post delivery. Results: Among 220 patients, 140 (63.6%) were primigravida and 80 (36.4%) were multigravida. Blood pressure was from 140/90 to 210/110mmHg average blood pressure was 175/100. 195 (88.63%) patients had deranged renal function tests and 215 (97%) patients had proteinuria >2+. At Three months post-delivery 151(68.6%) patients achieved normal blood pressure and 190 (86.3%) had normal serum creatinine i-e < 1.4. At six months 161 (73.8%) got adequate control of blood pressure, 59 (26.81%) had blood pressure > 140/90. Serum creatinine became in normal range in 195 (88.63%). Acute renal failure was observed in 6 patients who were put on renal replacement therapy.